Study the effect oxidation time on physical properties of cdo thin films prepared by thermal evaporated (Journal of the College of Basic Education, 2023)
thin films were prepared by thermal evaporated method of cadmium metal on a glass substrate, then conventional oxides in air at 500ᵒC and different oxidation times (30, 60 and 90) mint. The characterization of samples were carried out by atomic force microscopy and UV-VIS spectroscopy. Detailed optical and morphological properties of the prepared films are presented at different oxidation times. A UV-VIS transmition spectrum of produced films shows high transmission in visible, IR region and low transmission in UV region. Average grain size in the range of nanometer and decreases with increasing oxidation time.